Study on the Formation of Somites in Chick Embryo - Nurunnabi, ASM; Perven, HA; Shahriah, S; Rayhan, KA; Begum, GN; Begum, M; Hossain, MM (Journal of Dhaka Medical College, 2011)
Context: The chick embryo is used as a research model in developmental biology. The present study was designed to see the difference in the somite number evolution during the early embryogenesis in two hen breeds i.e. Local (deshi) hen and Plymouth Rock hen and to achieve a more profound knowledge of avian embryology as well as correlate with human early development. Study design: Descriptive type of study. Place and period of study: Histology and Embryology Laboratory, Department of Anatomy, Dhaka Medical College, Dhaka, from July to December 2004. Materials & Methods: The experiment was carried out on embryos groups at the age of 24, 36, 48, and 72 hours of incubation for two individual hen breeds. For each incubation period, 10 samples were prepared in the laboratory and studied in each breed. The number of somite was observed under the light microscope with low power objective and recorded for individual sample. Obtained data was statistically processed in order to quantify the influence of the genetic variation. Results: The number of somite found in Local (deshi) hen and Plymouth Rock (broiler) hen after 24 hours of incubation were 1.02±0.34 and 0.86±0.65, after 36 hours 12.26±2.14 and 10.24±2.58, after 48 hours 21.34±2.57and 18.62±0.84, after 60 hours 32.14±2.31and 29.82±2.72 and after 72 hours 41.66±2.24 and 39.89±2.95 respectively. Key words: Chick embryo; somite; early development; avian embryology. DOI: 10.3329/jdmc.v19i2.7083 J Dhaka Med Coll. 2010; 19(2) : 122-125